A novel combination of an IgE mediated adult onset food allergy and a suspected mast cell activation syndrome presenting as anaphylaxis. Issue 1 (December 2016) - Barber, Colin; Kalicinsky, Chrystyna
Abstract Background Adult onset food allergy is a rare, but increasingly recognized phenomenon. Mast cell activation syndromes present an ongoing diagnostic and classification challenge. The combination of the two has been rarely described in the literature. Case presentation We present a case of a new onset, IgE mediated food allergy in combination with a mast cell activation syndrome in an elderly patient not known to have a history of atopy. He presented to a hospital with a first presentation of anaphylaxis manifesting profound hypotension following consumption of a stew consisting of fish and shellfish. He had a persistently elevated serum tryptase and demonstrated evidence of high titre serum specific IgE to shellfish. He responded well to histaminergic blockade. Conclusions Given that mast cell activation syndromes pose an increased risk for recurrent, severe anaphylaxis and that secondary causes of mast cell activation syndromes are more prevalent with aging, this case highlights the importance of considering this entity when evaluating an elderly patient with a first presentation of anaphylaxis.